2019
DOI: 10.3390/colloids3010034
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transformation of Caffeic Acid on the Nanoceria Surface Studied by Temperature Programmed Desorption Mass-Spectrometry, Thermogravimetric Analysis and FT–IR Spectroscopy

Abstract: The studies of pyrolysis of caffeic acid (CA) and its surface complexes is important for the development of technologies of heterogeneous catalytic pyrolysis of plant- and wood- based renewable biomass components. In this work, the structure and thermal transformations of the surface complexes of CA on the surface of nanoceria were investigated using Fourier transform–infrared (FT–IR) spectroscopy, thermogravimetric analysis (TGA) and temperature-programmed desorption mass spectrometry (TPD MS). It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
2
16
0
1
Order By: Relevance
“…Calculated kinetic parameters indicate that these processes are also characterized by negative values of activation entropy. The formation of vinyl derivatives can be caused by the presence of silicon dioxide nanoparticles in lignin composition [22,23,24,25]. It is known that the accumulation of silica in plants occurs when ferulic acid is involved [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calculated kinetic parameters indicate that these processes are also characterized by negative values of activation entropy. The formation of vinyl derivatives can be caused by the presence of silicon dioxide nanoparticles in lignin composition [22,23,24,25]. It is known that the accumulation of silica in plants occurs when ferulic acid is involved [26].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the accumulation of silica in plants occurs when ferulic acid is involved [26]. There is a certain amount of cinnamic acids fragments conjugated with silica in lignin of rice husk, which can be revealed by the presence of an absorption band at 1696 cm −1 (Figure 1) caused by stretching vibrations ν C = O [23,25,26,27]. Cinnamic acids can interact with silica surface through both carboxylic and phenolic functional groups [23,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketenes formation has also been observed over Al2O3/SiO2, TiO2/SiO2 [41] and aluminosilicates due to the presence of Brönsted acid sites on their surfaces [50]. Cinnamic acids on the silica surface transform into corresponding ketenes, vinyl-and acetylene-benzenes via three parallel pathways b, e and f: ketenization, decarboxylation, and decarbonylation, [51][52][53]; whereas over the nanoceria surface, only the decarboxylation (f) takes place [54] [44]. A comparative study [41] of pyrolytic decomposition of valeric acid over SiO2, Al2O3, CeO2/SiO2, Al2O3/SiO2, and TiO2/SiO2 catalysts showed that propylketene forms on the surfaces of all these oxides except for CeO2/SiO2.…”
Section: Kinetic Studymentioning
confidence: 99%
“…At the same time, carboxylate bands appeared at 1396 (ν(CO)), 1410, 1440 cm −1 (νs(COO − )), and about 1502 and 1556 cm −1 (ναs(COO − )). The Δν values (Δν = νas(СОО − )−νs(СОО − ) [39,40]) were 62 and 146 cm −1 , and indicated the formation of bidentate carboxylate complexes with chelated and bridged structures. The ν(С=О) vibrations for monodentate complexes could be located The main absorption bands (Table 2) were assigned based on the literature data [16,[34][35][36][37][38].…”
Section: Fourier Transform-infrared (Ft-ir) Spectroscopymentioning
confidence: 99%